Comparative phytochemical evaluation of Ashodhit and Shodhit Bhallataka (Semecarpus anacardium L.f.) Using HPTLC and TLC Chromatographic profiling, UV-Vis spectroscopy study and 1H NMR based fingerprinting - Manas Ranjan Sahoo; Ramesh Raghava Varier; Anithakumari Rajendran; Bala Guru; S Srikrishan (Wolters Kluwer Medknow Publications, 2024)
Introduction: In Ayurveda, Shodhana is a method for purification or detoxification of some herbal drugs, minerals, and metals. Shodhana helps to remove or reduce the toxic properties of herbal drugs and enhances their therapeutic efficacy. Semecarpus anacardium Linn seeds (SA seeds) commonly known as Bhallataka is an important medicinal herb in Ayurveda. As the raw drug causes toxicity, it has to undergoes the Shodhana process to neutralize its toxic properties. Methods: In the present work, we studied transformation in chemical profiling of Shoodhit and Ashodhit Bhallataka (SA L.f) using high-performance thin-layer chromatography (HPTLC) profiling, thin-layer chromatography profiling, proton nuclear magnetic resonance (1H-NMR) fingerprinting, physicochemical analysis, and estimation of total phenolic and total flavonoids. The SA after Shodhana or purification process showed lesser oil contents as compared to raw drugs. Results: The Shodhana process led to the significant reduction of toxic fatty acid or oil content and reduction in the toxic phenolic components in the processed drug of SA L.f. The HPTLC profiling and 1H-NMR fingerprinting showed remarkable changes in the chemical profiling between the Shodhit and Ashodhit samples. The total phenolic and flavonoid content was found to be higher in unprocessed SA seeds than in the purified SA seeds. Conclusion: The study helps in the identification of the transformation of SA L.f. seeds concerning various chemical and physical attributes. The method used in the traditional medicine systems efficiently detoxify the raw drug of SA seeds. These approaches can be used in quality control analysis to ensure the effectiveness of Shodhana process.